Musa sapientum with exercises attenuates hyperglycemia and pancreatic islet cells degeneration in alloxan-diabetic rats - Akinlolu, Adelaja Abdulazeez (J Intercult Ethnopharmacol, 2015)
AIM: We tested the hypothesis that administrations of methanolic extracts of Musa sapientum sucker (MEMS) with exercises attenuated hyperglycemia in alloxan-diabetic rats. MATERIALS AND METHODS: A total of 40 adult male rats were divided into equal eight groups. Normoglycemic Group A was Control. Alloxan (180 mg/kg, i.p.) was administered to rats in Groups B - H to induce diabetes. Group B (diabetic control) received physiological saline. Groups C - H received MEMS (5 mg/kg), MEMS (10 mg/kg), Glibenclamide (5 mg/kg), MEMS (5 mg/kg) + exercises, MEMS (10 mg/kg) + exercises and Exercises only, respectively. Changes in body weight, blood glucose levels (BGL) and pancreatic histology were evaluated during or at the end of experiment. Body weights and BGL of rats were expressed as mean ± standard deviation and analyzed using the statistical software program SPSS 15. Statistical comparisons were done using the Student’s t-test for unpaired samples. Differences between groups were determined as significant at P ≤ 0.05. RESULTS: Significantly (P < 0.05) decreased bodyweight was observed in B and H compared to A and C - G. Treatment with MEMS significantly (P < 0.05) decreased elevated BGL in C and D. Hypoglycemic effect of MEMS appeared enhanced with exercises in F and G. Exercises regimen alone (H) resulted in percentage reduction in BGL lower than those of C - G. Histopathological examinations revealed normal pancreas (A), atrophied islet cells (B), hyperplasia with adequate population of islet cells (C - G), and reduced hyperplasia of islet cells (H). CONCLUSION: MEMS with exercises attenuated hyperglycemia in alloxan-diabetic rats.